(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Mangifera indica or commonly known as mango, is one of the 30 species of Mangifera genus from the family of Anacardiaceae. The fruit of M. indica is consumed for its antioxidant and health promoting activities in addition to its exotic flavor and texture. The present study was aimed to comparatively analyze the volatile constituents in the peel and pulp of M. indica cultivar Falan, Water Lily and Chok-anan. The mango peel and pulp were subjected to hydrodistillation using Clavenger type apparatus and the essential oils obtained were analyzed using GC-MS. There were 32 compounds identified in the essential oils of peel and pulp of three M. indica L. cultivars. Falan mango has the highest monoterpenes hydrocarbon composition in the essential oils of peel and pulp with 30.67% and 45.65%, respectively, whereas the essential oils of Water Lily mango are mainly dominated by the presence of sesquiterpenes hydrocarbon in both peel and pulp with 50.75% and 67.11%, respectively. The essential oils of Chok-anan mango are mainly consist of miscellaneous compounds in the peel and pulp with 22.56% and 44.1%, respectively. 4-Carene, b-caryophyllene, a-terpinolene, cyclohexadecane and n-hexadecanoic acid were the major volatile constituents in the essential oils of the three mango varieties.